Asymmetric real-time PCR detection of BRCA1 5382insC mutation by melting curve analysis in the LightCycler - Kroupis, C.; Christopoulos,K.; Devetzoglou,M.; Tsiagas,I.; Lianidou,E.S. (Clin.Chim.Acta, 2008)
BACKGROUND: 5382insC BRCA1 frameshift mutation is a common founder mutation for many populations worldwide and a high-risk allele for the development of hereditary breast and/or ovarian cancer. Our goal was to develop a novel, reliable and rapid method for its detection. METHODS: We developed an asymmetric real-time PCR method with hybridization probes in the LightCycler. Genotyping was performed by melting curve analysis. RESULTS AND CONCLUSIONS: The developed method was in concordance with reference methods when tested in 85 peripheral blood and 107 tumor DNA samples from Greek breast and/or ovarian cancer patients. The described method proved to be simple, cost-effective, easy to perform and rapid enough for routine use as a screening method in high-risk families and especially in the Greek, Slavic and Jewish populations where 5382insC mutation is the most common BRCA1 mutation
Keywords: analysis; Base Sequence; Blood; BRCA1 Protein; Breast Neoplasms; DNA Primers; Female; genetics; Greece; Humans; methods; Mutation; Ovarian Neoplasms; polymerase chain reaction